An Unusual Localization Of Spontaneous Gastric Perforation: A Case Report - Mert Demirel; Kürșat Karadayı; Savaș Serel; Murat Emiroğlu (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
A 75 year- old male patient was admitted to Plastic Surgery Department complained a painless mass on his left frontal skin area. Histopathological examination was diagnosed the squamose cell carcinoma of the scalp. The tumor was excised widely and reconstructed with a left Chinese free flap. An unlocalised epigastric pain and uncontrolled hiccups was started on the first day after the operation. A plain abdominal roentgenogram and computed tomography demonstrated a large amount free air under the diaphragm. A laparotomy was performed under the diagnosis of gastrointestinal perforation, a perforation of the posterior wall of the gastric fundus was found. The patient died due to myocardial infarct on postoperative ten days. Spontaneous gastric perforation is very rare condition.